PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SERTA IMPLIKASINYA PADA LOYALITAS KONSUMEN E-COMMERCE SHOPEE (Studi Kasus Produk Stein Cookware Di Jakarta Timur) - Cicih Ratnasih; Vivi Lusia; Mita Oktaviani (Jurnal Manajemen FE-UB, 2023)
This study aims to examine and analyze the effect of Product Quality and Price on Stein Cookware Purchase Decisions and the Implications for Shopee E-Commerce Consumer Loyalty in East Jakarta. The data used in this study are primary data taken from questionnaire responses. The population and sample used in this study were 100 respondents. Data analysis techniques in this study used the Classical Assumption Test, Path Analysis Test and Mediation Test (Sobel Test) which were processed using SPSS software version 26. The results showed that the influence of product quality had a positive and significant effect directly or indirectly through purchasing decisions on consumer loyalty, price had a positive and significant effect directly or indirectly through purchasing decisions on consumer loyalty and purchasing decisions had a direct positive effect on loyalty consumer. Keywords: Product Quality, Price, Purchase Decision, Consumer Loyalty.